Information and Communication Technology for Quality Assurance of Student Services in University of Ilorin and Al-Hikmah University - Akinnubi, Olaolu Paul; Alabi, Afusat Titilayo (International Journal of Educational Management, 2022)
The explosion in students enrolment posed to university managers in Kwara State is a great challenge and has made the application of ICTs indispensable for quality assurance of student services. Hence, this study was carried out to examine Information and Communication Technologies for quality assurance of student services in University of Ilorin and Al-Hikmah University. Descriptive research design was employed in the study. Three hundred and sixty four participants were selected as sample for the study using Research Advisors (2006). “Information and Communication Technologies for Quality Assurance of Student Services Questionnaire” (ICTQASSQ) was used to collect data for the study. The instrument was validated and a reliability coefficient of 0.76 was obtained through a pilot study. Two research questions and one research hypothesis guided the conduct of the study. Descriptive statistics of percentage and mean ratings were used to answer the research questions raised, while inferential statistic of t-test was used to test the research hypothesis formulated, at 0.05 level of significance. The findings of the study showed that there were ICT facilities for quality assurance services in the institutions. There was high level of implementation of ICT for quality assurance of student services at University of Ilorin and Al-Hikmah University with means of 1.75 and 1.71, respectively. There was no significant difference in ICT for quality assurance of student services between University of Ilorin and Al-Hikmah University (p-value = 0.299 > set p-value = 0.05). Based on the findings of the study, it was recommended, among others, that lecturers should embrace the use of ICT in teaching and, tutorials and group discussion among the students, and be encouraged by the institutions’ management to give lectures online.